DINAMIKA LEMAHNYA KRITISME MASYARAKAT TERHADAP NEPOTISME DI INDONESIA - Sugitanata, Arif (AL-BALAD : Jurnal Hukum Tata Negara dan Politik Islam, 2024)
This research aims to analyze the weak public criticism of the practice of nepotism in Indonesia through the Elite Theory perspective developed by Vilfredo Pareto and Gaetano Mosca. Nepotism, which is defined as giving important posts or positions to relatives or close friends without considering competence, has become an integral part of the Indonesian political system. This study uses descriptive qualitative research to explore the factors that influence people's attitudes towards nepotism and the interactions between these factors. Data sources were obtained through library research which included literature, articles and previous research. The research results show that the normalization of nepotism in Indonesia is strengthened by a paternalistic political culture, low community political participation, and economic dependence on political elites. The dominance of organized elites, as explained by Pareto and Mosca, plays a central role in weakening society's critical voice. Pareto emphasized that elites use nepotism to maintain power and hinder the circulation of new, more competent elites, while Mosca pointed out that elites manipulate public opinion and maintain the status quo through control over important resources and institutions. This condition results in apathy and the inability of society to form an effective opposition to the ruling elite. This research concludes that the weak public criticism of nepotism is a consequence of the dominance of elites who use their power to maintain control and avoid criticism. To overcome this problem, reforms are needed in the political and cultural system in Indonesia, including increasing transparency, strengthening anti-corruption institutions, as well as more inclusive and participatory political education. These findings provide a significant contribution to understanding the dynamics of power and social behavior in Indonesia and offer practical recommendations for strengthening the critical role of society in dealing with nepotism practices.